2015
DOI: 10.1097/scs.0000000000001913
|View full text |Cite
|
Sign up to set email alerts
|

Speech Articulatory Characteristics of Individuals With Dentofacial Deformity

Abstract: Differences regarding speed and stability of oral and laryngeal DDK were found among individuals with DFD compared with the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In total, 60 men aged 18–40 years [3, 12], 20 with Angle’s class III skeletal malocclusion (mean = 26.9 years, SD = 3.21) and 40 with Angle’s class I malocclusion (mean = 23.3 years, SD = 2.71) were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 60 men aged 18–40 years [3, 12], 20 with Angle’s class III skeletal malocclusion (mean = 26.9 years, SD = 3.21) and 40 with Angle’s class I malocclusion (mean = 23.3 years, SD = 2.71) were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Class III malocclusion affects the shape of the oral cavity, and thus, patients with class III malocclusion are expected to show differences in the structure of the vocal tract when compared to people with normal occlusion [2]. Those structural differences may affect voice and speech parameters because the tongue, which is the main articulator of speech, may undergo adaptations and impact the function of the hyoid-larynx complex during speech production [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal mandibular hypoplasia (SMH), presenting with small mandibular deformity, results in an unfavorable facial profile ( Hamid and Asad, 2003 ). In addition to affecting appearance, chewing, and pronunciation ( de Almeida Prado et al., 2015 , Maeda et al., 2008 ), severe SMH can cause narrowing of the pharyngeal airways, which results in obstructive sleep apnea syndrome (OSAS). OSAS increases the risks of cardiovascular disease, cerebrovascular events, depression, diabetes, and cognitive impairment, leading to poor life quality ( Bibbins-Domingo et al., 2017 , Gottlieb et al., 2010 , Kendzerska et al., 2014 , Peppard et al., 2006 , Yaggi et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, our study sample comprised patients with lateral mandibular deviation and class II and class III skeletal abnormalities. The shape of the oral cavity, movement of the tongue and length of the mandible are known to vary between the different types of malocclusion, and these structural differences may affect patients' voices (24,25). Previous studies have reported that individuals with class III malocclusions often encounter difficulty in producing labiodental and lingual-alveolar consonants (26).…”
Section: Discussionmentioning
confidence: 99%